Analysis of Factors that lead to poor Performance in Kenya Certificate of Secondary Examinations in Embu District, Kenya - Karue, Njagi; Amukowa, Wycliffe (My University, 2013)
This study was conceived on realization that day secondary schools performed below par in Kenya Certificate of Secondary Education in Embu District. It set to find out factors affecting performance in Kenya Certificate of Secondary Education in day secondary schools in Embu District of Eastern Province, Kenya. The input – output relationship or Education Production Function was used. The researcher used stratified random sampling while questionnaires were used to collect data. Data was analysed using descriptive statistics, multiple correlation and regression analysis. The SPSS statistical package was used to determine correlation and regression results. The factors which may affect performance in day secondary schools in the District include inter – alia unfavourable home environments and family backgrounds, which work negatively for students as they pursue their reading, lack of reading materials, chores at home, poor lighting, bad company, lack of proper accommodation, chronic absenteeism emanating from lack of school fees, admission of weak students at form one entry, inadequate instructional materials and physical facilities. The study makes far reaching recommendations to arrest the factors which affect performance of day secondary schools in Embu District. Among recommendations were that head teachers should as far as possible desist from sending students home for fees.
Keywords: Education; Performance; Examinations; Schools